Preparing Prospective Elementary Teachers to Teach Science: A Challenge for Teacher Education - Urban-Woldron, Hildegard (R&E-SOURCE, 2014)
Findings from educational research suggest that many primary school teachers admit a lack of science knowledge and confidence to teach it. In addition, attention to the attitudes of primary teachers toward science is of fundamental importance to research on primary science education. The paper reports on the evaluation of a science methods course for future primary science teachers guided by the framework of Pedagogical Content Knowledge (PCK) and also addressing students’ motivational orientations according to personal and teaching efficacy in science education. 158 pre-service primary science teachers took part in the study. Quantitative data were gathered from the STEBI-B and a content knowledge test. In addition, a set of qualitative data (portfolio, assignments, lesson plans, and reflection on teaching sequences) was used for answering the research question how the design of the course impacted the development of students’ PCK and motivational orientations. Starting with descriptive analyses, analyses of variance, confirmatory factor analyses, cluster analysis, and regression analysis were conducted. However, extensive data analyses reveal a range of alternative conceptions held by the pre-service primary teachers prior to the course. Generally, the pre-service teachers indicate positive self-efficacy beliefs regarding science teaching. In conclusion, no significant relationship between self-efficacy beliefs and achievement could be identified.